PSYCHO-SOCIAL FACTORS THAT INHIBIT LITERACY DEVELOPMENT IN THE PRIMARY SCHOOLS OF CAPRICORN DISTRICT, LIMPOPO PROVINCE - Inneth Baby Makofane; Medwin Dikwanyane Sepadi; Mahlapahlapana Themane (Annals of the University of Craiova for Journalism, Communication and Management)
This study aimed to investigate the psycho-social factors that inhibit or enable literacy development in the Foundation Phase in primary schools within the Capricorn District, Limpopo Province. The purpose of the study was to identify key psycho-social challenges that affect literacy acquisition and to propose strategies to create enabling environments for literacy development. A qualitative research approach was employed, using an exploratory case study design. Data was collected through semi-structured interviews with nine Foundation Phase teachers across three rural schools, as well as document analysis. Thematic analysis revealed five key findings